ANALISIS TEKNIK PERMAINAN GITAR ELEKTRIK JOHN MAYER PADA LAGU “SLOW DANCING IN A BURNING A ROOM” (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to identify and analyse the electric guitar techniques used by John Mayer in the song "Slow Dancing in a Burning Room" from the album Continuum (2006). The research uses a descriptive qualitative method with primary data consisting of video recordings of John Mayer's performances. The results show that in the intro and interlude, bending, vibrato, and slide techniques are found, which serve to build emotional nuance and a blues character. In the verse, hybrid picking, double stop, hammer-on, and pull-off techniques are found, enriching the harmonic texture and creating expressive legato playing. Overall, these techniques are used in a structured way to form a soft, soulful musical character with a modern blues vibe, which is a trademark of John Mayer's playing.